Screening for Cochleovestibular Disorders in Multiple Sclerosis : A Study of 100 Patients - Zantaoui, Ayoub; ZAKARIA, Yasmina; LAKHDAR, Youssef; CHEHBOUNI, Mohammed; OULGHOUL, Omar; BENHOUMMAD, Othmane; CHRAA, Mohamed; LOUHAB, Nissrine; ROCHDI, Youssef; RAJI, Abdelaziz (International Journal of Innovative Research in Medical Science, 2025)
ntroduction: Multiple sclerosis (MS) stands out as the most prevalent immune-mediated chronic inflammatory ailment affecting the central nervous system. It ranks among the primary causes of non-traumatic disability among the youth. The condition is characterized by the destruction of myelin and the impairment of oligodendrocytes in the brain, cerebellum, brain stem, and spinal cord. Its impact is predominantly observed in young individuals, with a notable prevalence among women. The clinical presentation is diverse and contingent on the affected structures. A definitive diagnosis relies on clinical and paraclinical criteria, assessing dissemination in time and space. Cochleovestibular damage is frequently reported by individuals with MS, either during the disease's course or as an initial presentation. Material and methods: We conducted a retrospective descriptive and analytical study of 100 patients being followed for multiple sclerosis in the neurology department of the Mohammed VI University Hospital of Marrakech, who underwent screening for cochleovestibular disorders in the otorhinolaryngology and Head and Neck Surgery department of the Mohammed VI University Hospital of Marrakech, over a 2-year period from January 2021 to December 2023. The audiometric evaluation consisted of pure tone audiometry, otoacoustic emissions(OAEs) and auditory brainstem response (ABR). We used videonystagmography (VNG), caloric tests and the Video Head Impulse Test (VHIT) for vestibular assessment. Results: The mean age of our patients was 32.8 years. Forty-five percent of patients presented with a cerebellar syndrome, 94% with a pyramidal syndrome, 55% with a spinal cord syndrome, 18% with proprioceptive impairment, and 36% with cranial nerve involvement. Among patients with cochleovestibular involvement, 9% had no lesions in the posterior fossa, 36% had lesions in the pontine and cerebellar peduncles, 23% in the cerebellum, 18% in the midbrain, 11% in the medulla, and 3% around the fourth ventricle. Deafness was the predominant symptom in 66% of cases, tinnitus in 46.6% of cases, and rotational vertigo was found in 33.33% of cases. Audiometrically, we performed a pure-tone audiogram for all our patients, showing mild deafness in 40% of cases, moderate in 27%, severe in 6%, and normal in 27% of cases. Acoustic otoemissions were positive in 67% of cases. The results showed that cochleovestibular disorders are common in MS patients and that they are not necessarily associated with lesions of the cochleovestibular nucleus or nerve. Conclusion This study represents an innovative initiative in Morocco, carried out by a multidisciplinary team comprising otorhinolaryngologists and neurologists. The findings from this research suggest that multiple sclerosis (MS) may exhibit diverse clinical manifestations throughout its progression, involving various peripheral and central structures, including those linked to cochleovestibular symptoms. The notably high incidence of such disorders observed in this study underscores the necessity for individuals presenting with these symptoms to undergo comprehensive evaluations, encompassing clinical, radiological, and electrophysiological tests, to rule out MS.